TBIO-28. DISEASEXPRESS, A CANCER DATA ANALYTICS AND VISUALIZATION TOOL FOR IDENTIFYING IMMUNOTHERAPEUTIC TARGETS IN PEDIATRIC BRAIN TUMORS AND OTHER CANCERS. Issue 2 (22nd June 2018) - Raman, Pichai; Rathi, Komal; Kalletla, Karthik; Zhu, Yuankun; Zhang, Bo; Cros, Anthony; Nazarian, Javad; Waanders, Angela J; Mueller, Sabine; Storm, Phillip B; Resnick, Adam C
Abstract: Identifying selective immunotherapy targets for clinical development in pediatric brain tumors poses a number of challenges. Growing publicly available datasets complemented by large scale cohorts of RNA sequencing data derived from cross-disease cohorts in the Children's Brain Tumor Tissue Consortium (CBTTC) and Pacific Pediatric Neuro-Oncology Consortium (PNOC) have provided for the development of novel, expression-based workflows designed to identify and prioritize tumor associated antigens for CAR-T, ADC, and mAB based therapeutic strategies for pediatric brain tumors and other cancers. In order to support such large-scale integrated analyses, we developed a data analytics and harmonized sequencing platform (DiseaseXpress) that overcomes a number of challenges. First, we compare our large-scale RNA sequencing based mRNA expression measures between tumors and a compendium harmonized normal mRNA (GTEx) to determine genes which are significantly differentially expressed overall or in a meaningful molecular subtype. We then couple this unbiased RNA sequencing-based discovery platform with a robust triaging step that includes the comprehensive validation of differential protein expression and tumor cell functional dependency. Together, implementing these workflows in DiseaseXpress provides for novel avenues for CAR-T target development and translation to a potently efficacious immunotherapeutic.